Depth of cure comparison of bulk-fill resin composites with two LED light-curing units: polywave versus monowave - Gutierrez-Leiva, Allan (2020)
Objective. To compare the depth of cure of three bulk-fill resin composites using polywave vs. monowave LED light-curing units. Methods. Cylindrical specimens (4 mm diameter and 10 mm height) were prepared using resin composites: Filtek One Bulk Fill Restorative (FO) (3M ESPE), Tetric N-Ceram Bulk Fill (TNC) (Ivoclar Vivadent) and Opus Bulk Fill APS (OP) (FGM), to evaluate the depth of cure according to ISO 4049 standard (n = 5). Two LED light-curing units were used: Bluephase N (Polywave, Ivoclar Vivadent) and LED D (Monowave, Woodpecker) with 24 J/cm2 of energy density. Data were analyzed by two-way Analysis of Variance and Tukey's post hoc test (α = 5%). Results. LED D group showed higher depth of cure values in all resin composites evaluated (p < 0.05). The values were: Bluephase N: 3.87 (TNC) > 3.74 (FO) > 3.31 (OP), and LED D: 4.29 (TNC) > 4.11 (FO) > 3.92 (OP). Conclusions. The monowave LED light-curing unit produced greater depth of cure than the polywave, regardless of the bulk-fill resin composite used. Resin composites showed different depth of cure values.